Perancangan Sistem Data Wirehouse untuk Meningkatkan Kinerja Pelayanan Bantuan Bagi Masyarakat pada Kantor Lurah Oebobo dengan Menggunakan Borland Delphi 7.0 - Hevi Herlina Ullu; Reany Yonanthi Mbeo; Donzilio Antonio Meko (Department of Information Technology, Universitas Timor, Indonesia, 2022)
Abstract - Computer technology represent important medium which used in various actifity management of governance. But that way the applications in computer technology still have common traits, and there is no application which in making special for the making of bank statement able to water down service of aid to society in braiding cooperation between governmental institution and society. Result of which obtaining from this research is a System Data of Warehouse able to in utilizing to assist increase service of aid to society which in the form of giving certificate.